Técnicas de estudio como estrategia metodológica para mejorar el proceso de aprendizaje en la asignatura de Ciencias Naturales, en los estudiantes del séptimo grado B, de la escuela de Educación General Básica Teniente Hugo Ortiz, de la ciudad de Loja. Periodo académico 2018-2019. Lineamientos Alternativos. - Angamarca Angamarca, Danilo Geovanny (2019)
The present research is about the Techniques of study as a methodological strategy to improve the learning process in the subject of Natural Sciences, in the students of the seventh grade B, of the Basic General Education Teniente Hugo Ortiz school, of the city of Loja. Academic period 2018-2019. Alternative Guidelines. The same one that has for general objective: to determine the techniques of study and its contribution in the development of the learning of the subject of Natural Sciences, of the students of the seventh grade B, of the school of Basic General Education Teniente Hugo Ortiz, academic period 2018 -2019. The type of study was descriptive, using the following methods: scientific, descriptive, observational, analytical, synthetic, inductive, deductive, hermeneutic and statistical; and the techniques of observation and survey. We worked with a population composed of 32 students and a teacher of the seventh grade B. At the conclusion of this research it is deduced that the study techniques facilitate the students' assimilation, comprehension, analysis and achievement of meaningful learning, so that its use is recommended in the process of learning the contents of the subject of Natural Sciences, with the aim of achieving an integral and quality education.